2020
DOI: 10.3390/jrfm13020033
|View full text |Cite
|
Sign up to set email alerts
|

A Principal Component-Guided Sparse Regression Approach for the Determination of Bitcoin Returns

Abstract: We examine the significance of fourty-one potential covariates of bitcoin returns for the period 2010–2018 (2872 daily observations). The recently introduced principal component-guided sparse regression is employed. We reveal that economic policy uncertainty and stock market volatility are among the most important variables for bitcoin. We also trace strong evidence of bubbly bitcoin behavior in the 2017–2018 period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In order to identify the most important variables that determine the returns of the most traded cryptocurrencies, we apply principal component-guided sparse regression (PC- LASSO, Tay et al 2018) following Panagiotidis et al (2020). This is a new method for large data to shrink predictions toward the most important principle components of the feature matrix by combining LASSO sparsity penalty with a quadratic penalty.…”
Section: Pc-lassomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the most important variables that determine the returns of the most traded cryptocurrencies, we apply principal component-guided sparse regression (PC- LASSO, Tay et al 2018) following Panagiotidis et al (2020). This is a new method for large data to shrink predictions toward the most important principle components of the feature matrix by combining LASSO sparsity penalty with a quadratic penalty.…”
Section: Pc-lassomentioning
confidence: 99%
“…We use a principal component-guided sparse regression (PC-LASSO) model of Tay et al (2018) for the identification of the most important variable. In the literature for cryptocurrencies, LASSO based models are employed by Panagiotidis et al (2018), observing that search intensity, gold returns and policy uncertainty are the most important variables for Bitcoin returns; and by Panagiotidis et al (2020), observing that policy uncertainty and stock market volatility are among the most important variables out of forty-one variables for the identification of Bitcoin returns using several subperiods of the overall period of 2010-2018. In this study, we use PC-LASSO to identify the most important variables regarding the returns of top five cryptocurrencies for the pre and post break point.…”
Section: Introductionmentioning
confidence: 99%
“…In [34,35] a continuous time model for Bitcoin price dynamics is studied to detect bubbles; regarding the existence of a bubble, in [36] it is proved it holds from early 2013 to mid-2014, but, not in late 2017 as supposed. Evidence of bubbly Bitcoin behaviour, mainly in the 2017-2018 period, is shown in [37], where it is also proved that economic policy uncertainty and stock market volatility play the most important role in Bitcoin values.…”
Section: Introductionmentioning
confidence: 94%
“…According to Kristoufek (2014), the formation of Bitcoin prices cannot be explained by standard economic theories, such as the discounted cash flow model, purchasing power parity, or uncovered interest rate parity, as there are several features of foreign currency supply and demand. Therefore, the most extensive research was carried out on possible internal and external factors affecting the price of cryptocurrencies, particularly the most famous Bitcoin cryptocurrency (Panagiotidis et al 2019;Poyser 2017;Kavvadias 2017;Letra 2016;Hayes 2015;Kristoufek 2014;. Panagiotidis et al (2019) concluded that uncertainty in economic policy and stock market volatility are among the most important variables between 41 examined potential drivers of Bitcoin returns.…”
Section: Overview Of the Previous Researchmentioning
confidence: 99%
“…Therefore, the most extensive research was carried out on possible internal and external factors affecting the price of cryptocurrencies, particularly the most famous Bitcoin cryptocurrency (Panagiotidis et al 2019;Poyser 2017;Kavvadias 2017;Letra 2016;Hayes 2015;Kristoufek 2014;. Panagiotidis et al (2019) concluded that uncertainty in economic policy and stock market volatility are among the most important variables between 41 examined potential drivers of Bitcoin returns. Internal and external factors affecting the Bitcoin price were defined by Poyser (2017) in his research.…”
Section: Overview Of the Previous Researchmentioning
confidence: 99%